On some formulae for ramanujan's tau function (2010)
Some formulae of Niebur and Lanphier are derived in an elementary manner from previously known formulae. A new congruence formula for $τ(p)$ modulo $p$ is derived as a consequence. We use this congruence to numerically investigate the order of $τ(p)$ modulo $p$.